ISLAMISASI DAN PROTOTIPE INSTITUSI - INSTITUSI PENDIDIKAN ISLAM DI INDONESIA - Muslih Hidayat (STAI Bumi Silampari, 2019)
This paper seeks to describe the topic of Islamization and embryo of Islamic education institutions in Indonesia by exploring the sources of related literature. On the subject, the author tries to find and construct theories relating to the historical-sociological process of Islamization in Indonesia ?; what is the relationship between Islamization and the growth and development of Islamic institutions, especially Islamic education institutions ?; what is the role of the Islamic kingdom in Islamization and the early development of Islamic education in the archipelago? The development of Islamic education institutions has attracted the attention of experts both from within and outside the country to conduct comprehensive scientific studies. Now there are many research works by experts that inform about the growth and development of educational institutions, especially Islamic education. The aim is to enrich the treasure of Islamic nuances of knowledge as well as a reference and comparison for managers of Islamic education in the following periods.